2020
DOI: 10.1111/tct.13318
|View full text |Cite
|
Sign up to set email alerts
|

A Springboard for physicians returning to practice

Abstract: Physicians commonly take time out of training for a number of reasons including parental leave, health-related absence and approved learning opportunities in research, education, leadership or other disciplines that nurture personal development. 1 In England, approximately 10% of doctors training to be consultants (specialists) are currently on such approved out of programme training opportunities with higher percentages in medical specialties. 2 The longer a clinician is out of programme, the more likely they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We consider this is a very valuable insight about the necessity of continuing medical education 21. It has been demonstrated that physicians who pause training have decreased confidence and poor performance ratings on their return 22. On this subject, clinical refresher courses may be useful at restoring clinical skills to a level comparable to their contemporaries23; this is important regardless of whether the applicant gets into a medical residency programme.…”
Section: Discussionmentioning
confidence: 95%
“…We consider this is a very valuable insight about the necessity of continuing medical education 21. It has been demonstrated that physicians who pause training have decreased confidence and poor performance ratings on their return 22. On this subject, clinical refresher courses may be useful at restoring clinical skills to a level comparable to their contemporaries23; this is important regardless of whether the applicant gets into a medical residency programme.…”
Section: Discussionmentioning
confidence: 95%
“…This program trained 540 doctors between 2014 and 2019, not an insignificant number of physicians returning to work. 5 It is a 2day training program reintroducing them into practice. As far as we could find, no such program exists in the United States.…”
mentioning
confidence: 99%